2021
DOI: 10.3389/fnbeh.2021.613025
|View full text |Cite
|
Sign up to set email alerts
|

Extended Amygdala Neuropeptide Circuitry of Emotional Arousal: Waking Up on the Wrong Side of the Bed Nuclei of Stria Terminalis

Abstract: Sleep is fundamental to life, and poor sleep quality is linked to the suboptimal function of the neural circuits that process and respond to emotional stimuli. Wakefulness (“arousal”) is chiefly regulated by circadian and homeostatic forces, but affective mood states also strongly impact the balance between sleep and wake. Considering the bidirectional relationships between sleep/wake changes and emotional dynamics, we use the term “emotional arousal” as a representative characteristic of the profound overlap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 148 publications
0
22
0
Order By: Relevance
“…In the BNST projections to the VTA, we find that just over half of the neurons express some combination of two of the three neuropeptides, but again very few expressed all three. We also observed that nearly half of all the inputs to the VTA from the BNST do not express any of the three neuropeptides investigated here, suggesting that these neurons are likely to release other neuropeptides into the VTA, such as the endogenous opioids enkephalin, dynorphin, and nociceptin that are known to modulate neural activity in this region (Kash et al, 2015;Giardino and Pomrenze, 2021). Indeed, we previously identified a dynorphin-expressing BNST to VTA population that contributed to anxiety-like behavior, but not conditioned threat discrimination (Fellinger et al, 2021).…”
Section: Discussionmentioning
confidence: 82%
“…In the BNST projections to the VTA, we find that just over half of the neurons express some combination of two of the three neuropeptides, but again very few expressed all three. We also observed that nearly half of all the inputs to the VTA from the BNST do not express any of the three neuropeptides investigated here, suggesting that these neurons are likely to release other neuropeptides into the VTA, such as the endogenous opioids enkephalin, dynorphin, and nociceptin that are known to modulate neural activity in this region (Kash et al, 2015;Giardino and Pomrenze, 2021). Indeed, we previously identified a dynorphin-expressing BNST to VTA population that contributed to anxiety-like behavior, but not conditioned threat discrimination (Fellinger et al, 2021).…”
Section: Discussionmentioning
confidence: 82%
“…In addition, these results contrast with another study that showed that inactivation of BNST reduced TMT-induced fear-related behavior (Fendt et al, 2003). The BNST is composed of several genetically identifiable cell-types (Giardino and Pomrenze, 2021; Ortiz-Juza et al, 2021), therefore, one explanation for why our inactivation of one cell-type in the BNST did not reduce TMT fear-related behavior could be that a different cell-type is responsible for TMT induced fear-related behavior. Another possible explanation for our finding could be that bulk inhibition of Pnoc BNST neurons is not selective enough to modulate behavior.…”
Section: Discussionmentioning
confidence: 89%
“…The bed nucleus of the stria terminalis (BNST) is a genetically diverse hub of the extended amygdala (Giardino and Pomrenze, 2021; Ortiz-Juza et al, 2021), and is strongly implicated in human psychopathologies defined by alterations in arousal and motivational states (Straube et al, 2007; Walker et al, 2009; Yassa et al, 2012). Recently, we identified that the activity of a subpopulation of prepronociceptin -expressing neurons within the BNST ( Pnoc BNST neurons) directly correlates with rapid changes in physiological arousal (observed by increases in pupillary size) when mice are presented with motivationally salient predator and food odors (Rodriguez-Romaguera et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that the alBNST mediates stress-induced anxiety-like behavior through the CRH neural network coordinating with CeA ( Pomrenze et al, 2019 ; Yamauchi et al, 2018 ). The functional distinctions between the lateral and medial adBNST appear to go beyond stress and anxiety because opposing roles in motivated states via specific responses to aversive and rewarding stimuli are shown for BNST CRH and CCK neurons, respectively ( Giardino et al, 2018 ; Giardino and Pomrenze, 2021 ). A specialized role in feeding regulation by PKC-δ neurons in the BNSTov is also reported ( Schnapp et al, 2022 ; Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%